The inhibition of Src kinase suppresses the production of matrix metalloproteinases in from synovial fibroblasts and inhibits MAPK and STATs pathways - KehrIbar, Demet Yalcin; Ozgen, Metin; YolbaS, Servet; Yildirim, Ahmet; Turkmen, Nese Basak; Etem, Ebru Onalan; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: The purpose of this study was to investigate the antiarthritic potentials of the inhibition of Src kinase in vivo and in vitro settings. Materials and methods: Arthritis was induced by intradermal injection of chicken type II collagen combined with incomplete Freund's adjuvant (collagen induced arthritis [CIA] model) in Wistar albino rats. One day alter the onset of arthritis, dasatinib, a potent Src kinase inhibitor, (5 mg/kg/day) was given via oral gavage. Tissue Src, Fyn, MAPK and STAT mRNA expressions were determined by real-time polymerase chain reaction. On the other hand, fibroblast like synoviocytes (FLSs) were harvested patients with rheumatoid arthritis (RA) undergoing surgical knee joint replacement. FLSs were stimulated with cytokines and dasatinib was added in different concentrations. MMP -1, -3, and -13 levels in FLSs culture were determined by ELISA. Results: The tissue mRNA expressions of Src, Fyn, MAPK and STATs were increased in the arthritis CIA group compared to the control group. Their mRNA expressions in the CIA + dasatinib group were decreased and similar in the control group. In in vitro setting, MMP -1, -3, and -13 expressions from FLSs induced by IL-1 beta and TNF-alpha were increased, while dasatinib suppressed their productions from FLSs. Conclusion: The present study shows that the inhibition of Src kinase has antiarthritic potentials in both in vivo and in vitro settings. Src kinase inhibition may be candidate to further research in human RA.
Keywords: Rheumatoid arthritis; collagen induced arthritis; src kinase; matrix metalloproteinase